PENGEMBANGAN VARIASI LATIHAN SEPAK SILA UNTUK PESERTA EKSTRAKURIKULER SEPAKTAKRAW DI SD NEGERI WONODADI 1 KECAMATAN WONODADI KABUPATEN BLITAR - Umi Qoryatiningtyas; M. E. Winarno M. E. Winarno; Mulyani Surendra (Gelanggang Pendidikan Jasmani Indonesia, 2017)
Abstract: The aimed of this study is to develop variations of soccer practice so that students are easier to learn soccer (sepak sila). The research method used is research and development method. The result of the development of soccer practice in SDN Wonodadi 1 Blitar obtained the following data: (1) The result of expert evaluation in sepaktakraw obtained 100% percentage and can be used, (2) The result of expert coaching in sepaktakraw obtained percentage 81.25% and stated can be used, (3) Result of evaluation of media expert obtained by percentage 78,55% and stated can be used, (5) Result of small group trial obtained 89,71 percentage and expressed can be used, (6) result of large group trial obtained percentage 89,06 % And otherwise can be used. It is concluded that the product of variation of soccer practice in SDN Wonodadi 1 Blitar is feasible and practical to use.